Learner and Advisor Perceptions of Online Advising During a Pandemic - Jo Mynard; Satoko Kato; Scott J. Shelton-Strong (Studies in Self-Access Learning Journal)
In this article, the authors describe two research studies conducted during the COVID-19 pandemic, exploring the perceptions of online advising from the perspective of learners and learning advisors working in a self-access centre at a university in Japan. Advising is a one-to-one reflective dialogue between a learner and a learning advisor with the purpose of promoting learner autonomy. Advising normally takes place in person, and this article explores user perceptions and whether advisors are able to create an autonomy-supportive climate in a synchronous online setting. Although participants in both studies acknowledged challenges, overall online advising was conducted effectively, with learning advisors anticipating the needs of learners and utilising online tools accordingly. Although initially nervous about attending online sessions, learners felt positive emotions during and after the online session and felt supported by learning advisors.